The limits of liberalism: tradition, individualism, and the crisis of freedom - Mitchell, Mark T. (University of Notre Dame Press, 2019)
Preface -- Acknowledgments -- Introduction: surveying the landscape and defining terms -- The seventeenth-century denigration of tradition and a nineteenth-century response -- Michael oakeshott and the epistemic role of tradition -- Alasdair macintyre's tradition-constituted inquiry -- Michael polanyi and role of tacit knowledge -- The incoherence of liberalism and the response of tradition -- Afterword: a conservatism worth conserving, or conservatism as stewardship -- Notes -- Bibliography -- Index.